The role of the national case management system in achieving protection for vulnerable children in the Republic of Yemen 2024 AD-1446AH - Al-Humaidi, Abdulghani Abdulaziz Abdu Naji (Journal of Educational and Psychological Sciences, 2025)
This study aimed to know the role of the national case management system in achieving protection for vulnerable children in the Republic of Yemen. The researcher used the descriptive survey method: It is one of the forms of organized scientific analysis and interpretation to describe a specific phenomenon or problem and depict it quantitatively by collecting data and specific information and subjecting it to an audit study. To collect the data, the researcher used the questionnaire tool. The researcher reached a number of results, the most important of which are: that all three areas of study for the role of the national case management system in achieving protection for vulnerable children in the Republic of Yemen; There is a "medium" availability degree with an arithmetic mean (3.40), and a relative weight (68.36%) in the results of the answers of the study sample members, which numbered (245) respondents. The role of the national case management system in achieving protection for vulnerable children in the Republic of Yemen is a positive and tangible role in the field of "providing supportive recreational protection services", as this field came in first place in the results of the answers of the study sample members with a "high" availability degree and an arithmetic mean (3.65), and a relative weight (73.055%), The study recommended the need for the leadership of the National Case Management System for Vulnerable Children in the Republic of Yemen to focus on achieving protection for vulnerable children in the Republic of Yemen by providing humanitarian protection services and educational protection services and developing projects and programs that achieve this.